Do Consumers Care About Green Marketing Practices? Insight from a Developing Nation - Oyenuga Michael Oyedele; Marcus Garvey Orji; Ahungwa Agnes Iember (Budapest International Research and Critics University, 2023)
21st century organisations are becoming aware of the need to be eco-friendly and as such provide goods and services that are environmentally safe. Green marketing practices afford them to engage in several activities that are sustainable and safe, but do consumers really care? This study was carried out to find out if consumers actually care about green marketing practices using the various dimensions of green marketing-mix practices and how it affects the behaviour of consumers in a developing country, specifically, Nigeria. The study utilized the cross-sectional research design using the quantitative approach to investigate the effect between dimensions of green marketing-mix practices (green product and green price) and buying behaviour. Primary data using questionnaires were collected from consumers of Domino's Pizza, Kubwa, Abuja, Nigeria. Descriptive analysis of data utilized frequencies and percentage distribution, while inferential analysis utilized correlations and multiple regression and ANOVA. The study found that green product, green place had a positive and significant effect on consumer buying behaviour of consumers of Domino`s Pizza Kubwa, Abuja, Nigeria. However, green price was found to have positive but insignificant effect on the consumer buying behaviour. Consequently, the study concludes that green product is very important factor in enhancing consumer buying behaviour of Consumer of Domino`s Pizza Kubwa, Abuja Nigeria. The study, therefore, recommends among others that Domino`s Pizza Kubwa, Abuja should communicate the value of their green product so that consumers will be ready to purchase without hesitation, also should share what went into setting the cost at a higher level than those of competitors.